Formação de biofilme em reembasadores temporários para prótese dentária - Valentini, Fernanda (2012)
Opportunistic fungi are responsible for infectious diseases in oral cavity that rose in prevalence in the last years, especially in complete denture wearers. Thus, colonization and growth of Candida species and other microorganisms are of clinical importance. The aims of this study were (i) systematically review the literature to determine if there is a protocol of prevention or treatment of Candida colonization in denture liners and (ii) clinically assess how biofilm composition is affected by different materials, time and the presence of candidiasis in denture wearers. In vitro and in vivo studies were evaluated with regard to treatment and/or prevention of Candida colonization and biofilm formation in denture liners. Six databases were searched (Lilacs, Scopus, Pubmed / Medline, Scielo and Cochrane Database of Systematic Reviews) from 1950 to 2012 using the keywords denture liner , Candida , tissue conditioner , denture stomatitis and antifungal agents . For the in situ study, twenty-eight volunteers, half with candidiasis, half healthy but Candida carriers wearing complete dentures were selected to participate in this study. Biofilm formed on acrylic resin and temporary denture liners (silicone based and acrylic resin based) specimens mounted in the internal surface of the volunteers upper dentures were collected in two phases of 21 days. Specimens were randomly removed on days 7, 14 and 21. Representative samples of the specimens were analyzed by SEM in the various periods under evaluation. Colony forming units/mm2 of biofilm of mutans streptococci, lactobacilli, total microorganisms and Candida species were determined. Through the systematic review it was possible to observe that the incorporation of nystatin to prevent the disease and the immersion in sodium hypoclorite to disinfect denture liners was the most frequently found treatment. However, as the data was in general derived from in vitro studies, there is a high risk of bias. For the in situ study, non-albicans Candida species showed higher counts in the silicone-based denture liner in diseased patients (p=0,01). Patients with candidiasis showed higher counts of mutans streptococci after 7 days (p=0.0041), but this difference disappeared after 14-21 days of biofilm formation. Thus, silicone-based denture liners should be avoided in diseased patients, as they have shown 12 higher nonn-albicans Candida species, which are known to be more virulent and resistant to conventional therapies.